Incorporation of tomato leaf curl virus (Tolcv) resistance in bacterial wilt resistant tomato. - Koteswararao Yadav (Department of Olericulture, College of Horticulture, 2011)
Investigations on “Incorporation of Tomato Leaf Curl Virus (ToLCV) resistance in bacterial wilt resistant tomato” were undertaken in the Department of Olericulture, College of Horticulture, Vellanikkara during the period from January, 2009 to May, 2011. Eighty tomato genotypes collected from India and abroad were screened for ToLCV resistance of which 26 were found to be highly resistant under natural screening. Of these, 20 genotypes (LE-474, LE-635, LE-640, LE-658, LE-666, LE-667, Arka Ananya, IIHR-2195, IIHR-2196, IIHR-2197, IIHR-2198, IIHR-2202, IIHR-2747, TLBRH-1, TLBRH-6, Cherry Tomato, H-24, H-86, Hawaii-7998 and Rani) were highly resistant to ToLCV under both graft transmission and whitefly transmission there by confirming their resistance to ToLCV. Seventy six tomato genotypes were screened for bacterial wilt resistance in bacterial wilt sick plot. Spot planting with known suscept Pusa Ruby was done to confirm the presence of virulent bacteria in the field. Anagha, Sakthi, Mukthi, LE-1-2, LE-626 and LE-474 were resistant to bacterial wilt. Three additional sources of resistance were identified viz., LE-628, LE-640 and LE-649. Five bacterial wilt resistant genotypes (Anagha, Sakthi, Mukthi, LE-1-2 and LE-626) were crossed with seven ToLCV resistant genotypes (IIHR-2195, IIHR-2196, H-24, H-86, Hawaii-7998, LE-474 and LE-640) in a line x tester fashion. Thirty five F1 hybrids developed were screened for both ToLCV and bacterial wilt resistance. Thirty hybrids were highly resistant to tomato leaf curl virus (ToLCV) among the 35 hybrids. Sixteen F1 hybrids were resistant to bacterial wilt. There were 15 F1 hybrids which were resistant to both ToLCV and bacterial wilt. Line x tester analysis was performed to derive information on general combining ability and specific combining ability effects, gene action and heterosis. Good general combiners for different characters were identified. Among the F1 hybrids Anagha x LE-640 was the earliest to flower and earliest to harvest. Sakthi x LE-640 (1.4 kg/plant) gave the maximum yield among the hybrids and parents followed by Mukthi x H-86 (1.1 kg/plant) and LE-1-2 x Hawaii-7998 (1.06 kg/plant). Maximum number of fruits were produced by LE-1-2 x Hawaii-7998 (39.67 fruits/plant). The maximum sized fruits were produced by Anagha x IIHR-2195 (55.93 g) followed by Sakthi x LE-640 (55.78 g) and Sakthi x IIHR-2196 (55.09 g). F2 segregants of 35 crosses were screened for combined resistance to bacterial wilt and ToLCV. Thirty F2 segregants were resistant to both bacterial wilt and ToLCV. Mukthi x IIHR-2195-F2-47 (1.7 kg/plant) and Mukthi x IIHR-2195- F2-34 (1.5 kg/plant) were the highest yielders among the 30 segregants. Segregation pattern in F1, F2, B1 and B2 of the cross combination Pusa Ruby x IIHR-2195 revealed that the resistance to ToLCV in IIHR-2195 is controlled by a single dominant gene.